U.S. adult perceptions of the harmfulness of tobacco products: descriptive findings from the 2013–14 baseline wave 1 of the path study. (April 2019) - Fong, Geoffrey T.; Elton-Marshall, Tara; Driezen, Pete; Kaufman, Annette R.; Cummings, K. Michael; Choi, Kelvin; Kwan, Jonathan; Koblitz, Amber; Hyland, Andrew; Bansal-Travers, Maansi; Carusi, Charles; Thompson, Mary E.
Abstract: Introduction: This study is the first nationally representative survey of U.S. adults (18+) to examine perceptions of the relative harms of eight non-cigarette tobacco products. Methods: Data are from Wave 1 of the Population Assessment of Tobacco and Health (PATH) Study Adult Questionnaire, a nationally representative study of 32, 320 adults in the United States conducted from September 2013 to December 2014. Results: 40.7% of adults believed that electronic cigarettes were less harmful than cigarettes, and 17.8% of adults believed that hookah was less harmful than cigarettes. Those less knowledgeable about the health risks of smoking were more likely to believe that the non-cigarette products were less harmful than cigarettes. Current non-cigarette tobacco product users were more likely to perceive that product to be less harmful than cigarettes (except filtered cigars). There was a significant positive correlation between beliefs that cigarettes were harmful and the likelihood of using hookah; perceptions of the harmfulness of cigarettes was not associated with the likelihood of using any other product. Conclusions: Perceptions of harmfulness varied widely across non-cigarette tobacco products. E -cigarettes and hookah in particular are seen as less harmful compared to cigarettes. Highlights: E-cigarettes (40.7%) were most likely to be seen as less harmful than cigarettes Hookah (17.8%) was next most likely to be seen as less harmful than cigarettes Belief that cigarettes are harmful associated with using hookah Product users more likely to believe their product less harmful than cigarettes